Effects of Reputations and Satisfactions on Positive Word of Mouth Intentions and Switching Behaviors - Leonnard Ong (International Journal of Business Studies, 2018)
The increasing numbers of new Higher Education Institutions (HEIs) require HEIs to establish their positive reputation and customer satisfaction to both attract and retain students. This study aims to examine the effects of reputation and satisfaction on word of mouth (WOM) and switching behavior of students at the private University Jakarta. By employing structural equation modeling (SEM), we prove that satisfaction has a high direct and signiicant inluence on Word of Mouth (WOM) and switching behavior (.79 and .93). While reputation has a low direct effect on WOM and switching behavior (.16 and .00).The role of satisfaction as a mediating variable increases the indirect effect of reputation on WOM and witching behavior of .67 and .79. Further managerial implications are discussed.